La consegna dei testimoni tra letteratura e critica A partire da Nerval, Valéry, Foscolo, d'Annunzio - Curreri, Luciano (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2009)
At bottom, youth also - and perhaps primarily - serves this purpose: to make room for the other, that is deconstructing oneself with a view to a reconstruction that is always implied in such a perspective. Moreover, those who do not manage to do so when they are young will have greater difficulty making room for the gift of the other when they are old, unless they wish to identify with that gift, albeit threatening the survival of critical capacity with a belated and excessive display of the self to the other. (From the author's Foreword)